Zebrafish (Danio rerio) and Japanese Medaka (Oryzias latipes) as model species for evaluation of endocrine disrupting chemicals - Yamani, Suresh (2011)
Endocrine disrupting chemicals (EDCs) are anthropogenic compounds that have similar properties as endogenous hormones in vertebrates and they are capable of interfering with the endocrine system. EDCs have been detected in sewage receiving effluents from industries and livestock feedlots. Fish living in the recipients contaminated with EDCs are reported to have disturbed physiological homeostasis and reproductive disabilities. The deleterious effects have also been reported in amphibians, reptiles, aves and mammals including humans. The natural estrogen, 17